Features of the heroic epics of the Turkic peoples of Siberia - Zhiyembayeva Гульбахрам (Turkic Studies Journal, 2023)
The folklore of the Turkic peoples is extremely rich and diverse. In terms of genre, the Turkic epics are of considerable interest, which, being transmitted orally and in writing from generation to generation and which reveal the spiritual wealth and culture of the Turkic peoples. Heroic epics depicting historical facts, events, and martial traditions of the Turkic peoples are indicative in this context. The origins of heroic epics go back to ancient myths, heroic fairy tales, ancient legends, where mythological consciousness undergoes significant mental changes in the formation of heroic epics. Mythological motifs can be traced in heroic epics of the Turkic peoples of Southern Siberia, that represent a complex synthesis of ancient beliefs of the Turkic peoples, and the epics themselves glorify the glorious exploits of the Turkic peoples, many of which have a real historical basis. This article highlights the history of the epics (including heroic) of the Turkic peoples of Siberia, their systematic classification by origin, subject matter, plot composition, genre characteristics is carried out, plot motives, including mythological ones, are identified. It is assumed that shamanic myths are at the structural basis of the epics of the Turkic peoples of Siberia, as a result of which the structural frame and the plot of events in the myths are repeated in the epics together with various semantic changes.